Gesellschaftskritik und Gerechtigkeit - Demirović, Alex (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
Political parties and social movements activists refere to the notion of justice as founding principle of critism. Demirovi? argues that the norm of justice is not able to motivate criticism and action. The norm of justice plays an important role in professional moral philosophy as is the case in the approaches of Martha Nussbaum or John Rawls. The offer arguments for their claims to give people and states a moral perspective. But the claim of universality that is inherent in moral discourses, always fail. The implication is that people who expect moral philosophy to be an advising knowledge become disappointed and perplexed. This is confirmed by the outcome of empirical research on justice among workers. To explain the dilemma of justice – claiming for universality and being particularistic and part of historical state form – the article takes up arguments developed by Marx and Horkheimer on justice as an ideological form.